2021
DOI: 10.1017/s0007114521002956
|View full text |Cite
|
Sign up to set email alerts
|

Dietary and serum vitamin D and preeclampsia risk in Chinese pregnant women: a matched case–control study

Abstract: The effect of vitamin D (VD) on the risk of preeclampsia (PE) is uncertain. Few of previous studies focused on the relationship between dietary VD intake and PE risk. Therefore, we conducted this 1:1 matched case-control study to explore the association of dietary VD intake and serum VD concentrations with PE risk in Chinese pregnant women. A total of 440 pairs of participants were recruited during March 2016 to June 2019. Dietary information was obtained using a 78-item semi-quantitative food frequency questi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…In addition to antioxidant nutrients, vitamin D supplementation has been proposed for the prevention of PE, although evidence has been inconsistent [ 56 ]. Our previous research observed a negative relationship between dietary VD intake and PE risk [ 57 ]. Vitamin D is a regulator of inflammation and may affect the occurrence of PE by regulating maternal immune response and reducing the concentrations of proinflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to antioxidant nutrients, vitamin D supplementation has been proposed for the prevention of PE, although evidence has been inconsistent [ 56 ]. Our previous research observed a negative relationship between dietary VD intake and PE risk [ 57 ]. Vitamin D is a regulator of inflammation and may affect the occurrence of PE by regulating maternal immune response and reducing the concentrations of proinflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…The sample size of this 1:1-matched case–control study was calculated based on the OR estimated from previous studies (OR = 0.45) ( 29 ). A sample size of 134 was calculated based on the aforementioned assumptions.…”
Section: Methodsmentioning
confidence: 99%
“…This study was performed between March 2016 and June 2019 at the First Affiliated Hospital of Zhengzhou University, China. Full details about the study design have been published in previous studies (21)(22)(23) . In particular, a total of 466 cases with a ratio of 1:1 matched for case control were enrolled.…”
Section: Study Population and Study Designmentioning
confidence: 99%